Systemic amyloidosis associated with chronic lymphocytic leukemia/small lymphocytic lymphoma. Issue 5 (19th March 2013) - Kourelis, Taxiarchis V.; Gertz, Morie; Zent, Clive; Lacy, Martha; Kyle, Robert; Kapoor, Prashant; Zeldenrust, Steven; Buadi, Francis; Witzig, Thomas; Hayman, Suzanne; Lust, John; Russell, Stephen; et al.
<x xml:space="preserve">Abstract</x> To clarify the presentation and course of patients with chronic lymphocytic leukemia (CLL) and amyloidosis. Mayo databases were interrogated for patients who carried a diagnosis of amyloidosis and CLL evaluated at Mayo Clinic, Rochester from January 1974 to October 2012. Charts were abstracted and data analyzed. Of the 33 patients identified, 20 (61%) were diagnosed with AL and 13 (39%) with non‐AL. Only four patients had immunoglobulin light chain amyloidosis (AL) that could be solely attributed to the CLL clone; another six had both a plasma cell clone and a CLL clone that shared the same light chain. Median overall survival was 15.6 months for patients with AL and 58.1 months for patients with non‐AL. For patients with AL management involved chemotherapy targeted toward monoclonal plasma cells, lymphocytes or both, and for patients with non‐AL no specific amyloid treatment was administered. AL is a rare complication of CLL, but in this elderly population of patients non‐AL is nearly as common. Distinguishing between these two groups is essential since patients with non‐AL amyloidosis have better outcomes and they do not require cytotoxic chemotherapy to treat their amyloidosis. Am. J. Hematol. 88:375–378, 2013. © 2013 Wiley Periodicals, Inc.